1994
DOI: 10.1083/jcb.125.4.867
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-egg recognition in the mouse: characterization of sp56, a sperm protein having specific affinity for ZP3.

Abstract: Abstract. Recognition between mammalian gametes occurs when the plasma membrane of the sperm head binds to the zona pellucida (ZP), an extracellular coat surrounding eggs. ZP3, one of three glycoproteins in the ZP, is the egg protein recognized by sperm. A mouse sperm surface protein, sp56 (Mr = 56,000), has been identified on the basis of its specific affinity for ZP3 (Bleil, J. D., and P. M. Wassarman. 1990. Proc. Natl. Acad. Sci. USA. 87:5563-5567). Studies presented here were designed to characterize mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
98
2
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(102 citation statements)
references
References 20 publications
(36 reference statements)
1
98
2
1
Order By: Relevance
“…Capacitated Acr ϩ/ϩ and Acr Ϫ/Ϫ mouse sperm were treated with calcium ionophore A23187, and the time course of protein release from the acrosome was monitored by indirect immunofluorescent staining using two monoclonal antibodies against mouse acrosomal proteins (mAb sp56 (12,13) and mAb MC101 (8); Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Capacitated Acr ϩ/ϩ and Acr Ϫ/Ϫ mouse sperm were treated with calcium ionophore A23187, and the time course of protein release from the acrosome was monitored by indirect immunofluorescent staining using two monoclonal antibodies against mouse acrosomal proteins (mAb sp56 (12,13) and mAb MC101 (8); Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…75 Immunization of female BALB/c mice with E. coli-expressed recombinant Sp56 fusion protein led to sub-fertility. 76 However, sp56 null mice showed normal fecundity and thus undermining its role during fertilization.…”
Section: Sp56mentioning
confidence: 99%
“…ZP3R/sp56 was initially discovered by photoaffinity crosslinking with ZP3 (9) and later characterized as having specific affinity for mouse ZP3 oligosaccharides involved in sperm binding (10). The cloning of ZP3R/sp56 demonstrated that it is a member of the superfamily of C3/C4 binding proteins, possessing multiple short consensus repeats (so-called "sushi" domains) characteristic of complement regulatory proteins; however, the protein lacked an obvious carbohydrate recognition domain (8).…”
mentioning
confidence: 99%
“…ZP3R/sp56 is first detectable during late meiosis although during the course of spermatid differentiation, the acrosomal glycoprotein undergoes post-translational modifications, which may include the modification of carbohydrate side chains (14). Initial reports suggested that ZP3R/sp56 is a plasma membrane protein (10,15). However, our laboratory later demonstrated by conventional immuno-electron microscopy that ZP3R/sp56 is an intra-acrosomal protein and is, in fact, part of a stable acrosomal matrix (14,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation